Tracing woody-organic tsunami deposits of the 2011 Tohoku-oki event in Misawa (Japan) - Bellanova, Piero (Sci Rep, 2021)
With a minimum of three reported waves, the 2011 Tohoku-oki tsunami’s destructive force caused massive damage along the northern Japanese Aomori coast. At Misawa the coastal control area was inundated up to 550 m inland and sandy sediment remnants can be traced to c. 350 m (c. 61–63% of the maximum inundation) from the shoreline. Linking the discovery of floatable plastic objects within a woody and organic layer to our analytical data lead to the detection of a yet undocumented woody-organic tsunami deposit first appearing on top of the sandy deposit but then reaching even further inland (approx. 69–72% of the max. inundation). By this observation our understanding of the documented part of the tsunami inundation may be improved. As a consequence, sand sheets of historic and paleo-tsunamis represent minimum estimates for the coastal inundation and underestimation may be reduced by addressing the woody and organic fraction of a tsunami’s inundation.